Clinical and morphological aspects of the supernumerary teeth - Alves, N. [UNESP]; de Oliveira Nascimento, C. M.; Olave, E. (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2011)
The hyperdontia teeth is an anomaly of unknown cause, characterized by increased numbers of teeth. It occurs more frequently in the maxilla, preferably in males, and is more common in permanent dentition. The presence of supernumerary teeth can be responsible for alterations in the permanent dentition, such as the delay in the eruption and dislocations. In addition, the patient may have abnormal occlusion, resorption of adjacent teeth and cyst formation. This article describes in a male patient, 9 years old, the presence of two upper right lateral incisor and one upper left lateral incisor, permanent, partially erupted. Radiological examination revealed a second left upper lateral incisor, unerupted. It should be noted that both, in the region of the 1.2 as in 2.2, the teeth showed normal anatomy and not the conoid appearance commonly observed in supernumerary teeth. In our case, in order to perform orthodontic treatment surgical removal of the teeth noted above was indicated.
Aspectos clínicos y morfológicos de los dientes supernumerarios
Keywords: Anatomy; Dental anoma; Mixed dentition; Supernumerary teeth; Supplemental lateral incisors